IEEE INFOCOM 2014 - IEEE Conference on Computer Communications 2014
DOI: 10.1109/infocom.2014.6848121
|View full text |Cite
|
Sign up to set email alerts
|

Practical DCB for improved data center networks

Abstract: Storage area networking is driving commodity data center switches to support lossless Ethernet (DCB). Unfortunately, to enable DCB for all traffic on arbitrary network topologies, we must address several problems that can arise in lossless networks, e.g., large buffering delays, unfairness, head of line blocking, and deadlock. We propose TCP-Bolt, a TCP variant that not only addresses the first three problems but reduces flow completion times by as much as 70%. We also introduce a simple, practical deadlock-fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(26 citation statements)
references
References 19 publications
1
23
0
Order By: Relevance
“…Some recent proposals aim to overcome these issues with PFC using ECN markings to maintain low queue occupancy. TCP-Bolt [14] uses modified DCTCP algorithm within the kernel TCP stack. DCQCN [48] uses a combination of ECN markings with a QCN-inspired rate-based congestion control algorithm implemented in the NIC.…”
Section: Related Workmentioning
confidence: 99%
“…Some recent proposals aim to overcome these issues with PFC using ECN markings to maintain low queue occupancy. TCP-Bolt [14] uses modified DCTCP algorithm within the kernel TCP stack. DCQCN [48] uses a combination of ECN markings with a QCN-inspired rate-based congestion control algorithm implemented in the NIC.…”
Section: Related Workmentioning
confidence: 99%
“…D 2 TCP [50] builds upon DCTCP to prioritize flows based on deadlines. TCP Bolt [49] uses flow-level congestion control via ECN to address PFC's limitations. ICTCP [51] iteratively adjusts the TCP receive window before incastinduced packet drops.…”
Section: Related Workmentioning
confidence: 99%
“…Recent work has shown that, replacing PFC with IRN helps DCQCN but does not remove the need for congestion control [22]. DCTCP [3] and TCP Bolt [32] are software sender-based congestion control schemes. These support selective retransmission but have higher CPU overhead and latency than RDMA hardware.…”
Section: Related Workmentioning
confidence: 99%
“…(iv) Our evaluation is limited to RDMA congestion control algorithms. We believe our hop-by-hop approach will compare favorably to TCP congestion control [3,32], but we do not present a quantitative comparison at this time.…”
Section: Introductionmentioning
confidence: 98%